Role of Obesity in Human Health and Disease - Rao, Venketeshwer; Rao, Leticia; Rao, Venketeshwer; Rao, Leticia (IntechOpen, 2021)
Many factors influence obesity including genetic, environmental, and lifestyle factors. Studies have shown obesity to be related to increased risk of human diseases. Despite efforts by health professionals to regulate obesity, its prevalence has increased globally in the past few decades. A better understanding of the causes of obesity and mechanisms by which obesity increases the risk of human diseases can lead to developing effective strategies that can save many lives worldwide. This book addresses some important aspects of the relationship between obesity and human health. Chapters cover such topics as body mass index, endocrine disorders, obesity, and endometrial cancer, the role of lifestyle factors in obesity, and much more.
English
Keywords: Public health & preventive medicine